Virtual Generation of Lidar Data for Autonomous Vehicles - Alldén, Tobias; Chemander, Martin; Jansson, Jonathan; Laurenius, Rickard; Davar, Sherry; Tibom, Philip (My University, 2017)
The area of autonomous vehicles is a growing field of research which has gained popularity in the later years. Companies such as Tesla and Volvo continuously work on creating vehicles that can autonomously navigate traffic with the use of different sensors and algorithms. However, given the cost and risks of testing these in real world scenarios there may be a need for simulation tools in which the algorithms can be tested during development without the need for a real autonomous car. Thus opening the area of research for independent researchers and other actors with limited financial means. This thesis presents the creation of such simulation tools. It is shown that sufficiently realistic simulation tools can be created using the game engine Unity along with free assets from the unity asset store. The simulation can be run on an off-the-shelf computer with good results. However, some aspects that can influence the resolution of the sensor in real life scenarios, such as weather conditions are not implemented.
Keywords: Data- och informationsvetenskap; Computer and Information Science